Solomonic Magic : Methodology, Texts, and Histories - Sofer, Gal, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2025)
Solomonic magic has captivated imaginations for centuries, yet its definition remains elusive. Is it a specialized branch linked to King Solomon, or a broader classification of practices attributed to him? This book explores the mysterious world of demon subjugation, examining previously unknown texts in multiple languages (Aramaic, Hebrew, Greek, Latin, and more) to reveal the historical evolution of this magical tradition. Divided into three parts, the book presents analyses of key manuscripts and examines the historical influence of Hebrew texts on later traditions. Featuring many unpublished manuscripts, this book challenges previous scholarly assumptions and offers a new perspective on the textual network that shaped medieval and early modern magical works.